Non-specific effects of BCG and DTP vaccination on infant mortality: An analysis of birth cohorts in Ghana and Tanzania. Issue 27 (15th June 2022) - Quinn, MK; Edmond, Karen M.; Fawzi, Wafaie W.; Hurt, Lisa; Kirkwood, Betty R.; Masanja, Honorati; Muhihi, Alfa J.; Newton, Sam; Noor, Ramadhani A; Williams, Paige L.; Sudfeld, Christopher R.; Smith, Emily R.
Highlights: BCG vaccination was associated with decreased risk of infant mortality in Tanzania and Ghana. DTP was also associated with decreased risk of infant mortality. There was no evidence of interaction between DTP or BCG vaccination, neonatal vitamin A supplementation, and infant sex on infant survival. Abstract: Background: Vaccines may induce non-specific effects on survival and health outcomes, in addition to protection against targeted pathogens or disease. Observational evidence suggests that infant Baccillus Calmette-Guérin (BCG) vaccination may provide non-specific survival benefits, while diphtheria-tetanus-pertussis (DTP) vaccination may increase the risk of mortality. Non-specific vaccine effects have been hypothesized to modify the effect of neonatal vitamin A supplementation (NVAS) on mortality. Methods: 22, 955 newborns in Ghana and 31, 999 newborns in Tanzania were enrolled in two parallel, randomized, double-blind, placebo-controlled trials of neonatal vitamin A supplementation from 2010 to 2014 and followed until 1-year of age. Cox proportional hazard models were used to estimate associations of BCG and DTP vaccination with infant survival. Results: BCG vaccination was associated with a decreased risk of infant mortality after controlling for confounders in both countries (Ghana adjusted hazard ratio (aHR): 0.51, 95% CI: 0.38–0.68; Tanzania aHR: 0.08, 95% CI: 0.07–0.10). Receiving a DTP vaccination was associated with a decreased risk of death (Ghana aHR: 0.39, 95% CI: 0.26–0.59; Tanzania aHR: 0.19, 95% CI: 0.16–0.22). There was no evidence of interaction between BCG or DTP vaccination status and infant sex or NVAS. Conclusion: We demonstrated that BCG and DTP vaccination were associated with decreased risk of infant mortality in Ghana and Tanzania with no evidence of interaction between DTP or BCG vaccination, NVAS, and infant sex. Our study supports global recommendations on BCG and DTP vaccination and programmatic efforts to ensure all children have access to timely vaccination. Clinical trials registration: Ghana (Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12610000582055) and Tanzania (ANZCTR: ACTRN12610000636055)